Effect of Concept Mapping Strategy on Concept Retention and Concept Attrition in Organic Chemistry - Sharma, Kanak (JOURNAL OF INDIAN EDUCATION, 2013)
This paper reports on a quasi-experimental study which was conducted to compare the effect of Concept mapping strategy and Conventional teaching method on concept retention and concept attrition among Class XII science students in Organic Chemistry. For this reason the achievement test scores in Organic Chemistry of the Class XII science students from an English Medium school at Varanasi (U.P.), affiliated to CBSE who were taught “Ketone” in Chemistry course either using Conventional teaching method (Control Group or Group A) or Concept mapping strategy (Experimental Group or Group B), were analysed. The results of the present study indicates that Concept mapping strategy is significantly more effective than the Conventional method in the improvement of achievement in Organic Chemistry, concept retention in Organic chemistry and for preventing concept attrition (retention loss) in Organic Chemistry.